2017
DOI: 10.21037/tlcr.2017.07.05
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of circulating tumour cells in patients with small cell lung cancer

Abstract: Small cell lung cancer (SCLC) accounts for 15% of lung cancer diagnosed worldwide. It is aggressive and characterised by early metastatic spread with rapid development of chemo resistance such that less than 5% of patients diagnosed survive 5 years. Surgery is rarely performed and failure to identify new effective treatments has been attributed in a large part to lack of good quality tumour biopsies available for translational research. Liquid biopsies provide a minimally invasive alternative to traditional tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 55 publications
0
21
2
Order By: Relevance
“…Serial sampling would give information on disease burden, responses to treatment and on disease relapse. Promising results have been obtained with circulating tumor cells (CTCs) [14] , but there is a large variation in CTC numbers and heterogeneity in the expression of NCAM [14] . Our present strategy is to use tumor derived extracellular vesicles (EVs) as a correlate of tumor load.…”
Section: Discussionmentioning
confidence: 99%
“…Serial sampling would give information on disease burden, responses to treatment and on disease relapse. Promising results have been obtained with circulating tumor cells (CTCs) [14] , but there is a large variation in CTC numbers and heterogeneity in the expression of NCAM [14] . Our present strategy is to use tumor derived extracellular vesicles (EVs) as a correlate of tumor load.…”
Section: Discussionmentioning
confidence: 99%
“…CTCs play a relevant role in small cell lung cancer (SCLC). In particular, CTCs were detectable in about 70–95% of patients with SCLC [40, 41]. The identification of CTCs may play an important role in the early detection of SCLC [40].…”
Section: Circulating Tumour Cellsmentioning
confidence: 99%
“…In particular, CTCs were detectable in about 70–95% of patients with SCLC [40, 41]. The identification of CTCs may play an important role in the early detection of SCLC [40]. In the experience by Ilie et al [42], the authors showed that all patients with the identification of CTCs developed a pulmonary nodule during the follow-up and before CT identification.…”
Section: Circulating Tumour Cellsmentioning
confidence: 99%
See 2 more Smart Citations